Cell therapy for a rare disease- hairy cell leukemia variant - Claire Fritz; Derek P Wong; Philip Rock; Richard Burack; Akshaya Radhakrishnan; Reshmi Parameswaran (OncoImmunology, 2024)
Hairy cell leukemia variant (HCL-v) is a rare malignancy of clonal mature B-cells that follows a chronic disease course. HCL-v patients are often resistant to purine nucleoside analogs, which are the first-line therapy. To address the shortcomings of current therapy for HCL-v, we investigated the activity of a BAFF ligand-based CAR-T cell which binds to all three BAFF receptors, BAFF-receptor, TACI, and BCMA. Here, we demonstrate that HCLv patient-derived cells highly express all three BAFF receptors and that BAFF CAR-T cells induce significant cytotoxicity in vitro against both cell lines and HCL-v patient cells. This cytotoxicity corresponds with significant CAR-T cell activation, degranulation, and release of pro-inflammatory cytokines after co-incubation with HCLv cells. Furthermore, we successfully generated BAFF CAR-T cells directly from an HCLv patient and observed direct autologous killing against patient tumor cells in vitro. These HCLv patient-derived CAR-T cells were also effective in killing the Hair-M cell line and tumor cells derived from a different HCLv patient. Lastly, we also developed two mouse xenograft models for HCL, a subcutaneous Bonna-12 model and intravenous Hair-M xenograft model. We observed decreases in tumor burden and prolonged overall survival without significant toxicity. In conclusion, here we show that BAFF CAR-T cells exert anti-tumor effects in vitro and in vivo against multiple cell lines and patient-derived HCL-v samples and may be a successful therapeutic strategy for HCLv patients.